PENGARUH PENERAPAN MULTIMEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 43 PADANG - Azwan, Dina Aulia (Jurnal Edukasi dan Penelitian Matematika, 2023)
The level of mastery of mathematics that has been obtained during learning can be reflected by the learning outcomes. The problem that occurs at SMP Negeri 43 Padang is the low mathematics outcomes of learning achieved by students. The use of interactive learning multimedia is the solution that is applied in this problem. This study aims to know differentiate between interactive multimedia-based learning and learning by conventional. This research uses the type of quasi-experimental with a nonequivalent posttest-only control group design. The research population are students of 8th grade of SMP Negeri 43 Padang, with VIII 1 as the class for experimental and VIII 3 as the class for control, the choosing by technique of purposive sampling. The research instrument that used in this research is essay questions form test of learning outcomes from mathematics. The research hypothesis is analyzed by t-test. P-value = 0,000 at significance level ? = 0,05 is obtained based on the data analysis result so that ?0  is rejected. Therefore, we got the conclussion that students who study using interactive learning multimedia obtain better learning outcomes by mathematics than students who study by learning with conventional. Keywords – interactive learning multimedia, learning outcomes, Cartesius